PENGARUH PENGINTEGRASIAN DAN PERENCANAAN STRATEGIS TERHADAP KINERJA PEGAWAI PADA BALAI BESAR WILAYAH SUNGAI SUMATERA VIII YANG BERGERAK DI BIDANG IRIGASI DAN RAWA II KOTA LUBUKLINGGAU - Murlina Nisusmiati (Jurnal Media Ekonomi (JURMEK), 2016)
The purpose of the study was to determine the effect of integration and strategic planning on employee performance at the Central Sumatra River Region VIII which is engaged in Irrigation and Swamp II in Lubuklinggau City. The population in this study were all employees totaling 30 people. This study uses saturated samples by taking all employees. The results of the multiple regression equation are obtained: Y = 0.237 + 0.483 X1 + 0.517 X2. Based on the results of the F test shows a significant number of probability Fcount of 48.215 abel Ftable 3.35 significance level 0,000 <α = 0.05 so that it can be concluded that integration and strategic planning have a significant effect on employee performance at the Central Sumatra VIII River Region engaged in Irrigation and Rawa II Lubuklinggau City. The determination coefficient of 0.781 means integration (X1) and strategic planning (X2) together to contribute to employee performance (Y).